The effects of machining on the microstructure and transformation behavior of NiTi Alloy - KAYNAK, YUSUF (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
This study presents evidence of a machining-induced deformation layer in a NiTi shape memory alloy and the subsequent effect of this layer on the underlying transformation behavior of the material. Severe twinning-induced deformation was observed in the substrate of samples pre-cooled and machined by orthogonal cutting under cryogenic conditions, while (1 1 4)(B2)-type deformation twinning and significant dislocation activity was observed after dry machining of the NiTi. In addition, cryogenic machining resulted in a much deeper affected zone than machining under dry conditions. (C) 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: NiTi; Shape memory alloys; Cryogenic machining; Machining-induced layer; Twinning deformation; SHAPE-MEMORY ALLOY; CHANNEL ANGULAR EXTRUSION; DEFORMATION; TI50NI47FE3; MARTENSITE